2004
DOI: 10.1111/j.1365-2958.2004.04051.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of host‐encoded nucleoid proteins on transposition: H‐NS influences targeting of both IS903 and Tn10

Abstract: SummaryNucleoid proteins are small, abundant, DNA-binding proteins that profoundly affect the local and global structure of the chromosome, and play a major role in gene regulation. Although several of these proteins have been shown to enhance assembly of transpososomes before initiating transposition, no systematic survey has been carried out examining the in vivo role(s) of these proteins in transposition. We have examined the requirement of the six most abundant nucleoid proteins in transposition for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 60 publications
3
77
0
Order By: Relevance
“…One expectation of this hypothesis is that the intermolecular transposition frequency would be reduced in the hns12 strain because instead of the vast majority of H-NS-interacting transpososomes going on to form intermolecular STPs, some fraction of these would be partitioned to the intramolecular pathway to give knotted inversion circles. In support of this we have found that in a papillation assay (Swingle et al 2004), intermolecular transposition events were greatly reduced in the hns12 strain (data not shown).…”
Section: Does H-ns Promote Tn10 Transposition In Vivo By Inducing Trasupporting
confidence: 69%
See 3 more Smart Citations
“…One expectation of this hypothesis is that the intermolecular transposition frequency would be reduced in the hns12 strain because instead of the vast majority of H-NS-interacting transpososomes going on to form intermolecular STPs, some fraction of these would be partitioned to the intramolecular pathway to give knotted inversion circles. In support of this we have found that in a papillation assay (Swingle et al 2004), intermolecular transposition events were greatly reduced in the hns12 strain (data not shown).…”
Section: Does H-ns Promote Tn10 Transposition In Vivo By Inducing Trasupporting
confidence: 69%
“…In IS1 transposition, H-NS promotes transposition as it affects the amount of transposase (InsAB protein) produced, either by aiding in InsAB translation or by protecting InsAB from proteolysis (Rouquette et al 2004). H-NS also promotes IS903 and Tn552 transposition, but it is not yet known how it acts in these systems (Swingle et al 2004). It seems unlikely that H-NS would influence IS903 or Tn552 transposition via the same mechanism as that proposed here for Tn10 transposition because there is no evidence for IHF-mediated transpososome unfolding in these systems and they lack obvious IHF-binding sites close to the terminal inverted repeats (Derbyshire and Grindley 1992;Leschziner et al 1998).…”
Section: Impact Of H-ns On Other Transposition Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows investigation of a host mutation which disturbs the stability or mobility of the plasmids. It was reported that change of the local and global structure of the chromosome induced by binding of nucleoid proteins or chromosomal DNA replication affects target site selection of transposons (Peters and Craig, 2000;Swingle et al, 2004). The GFP hop-on assay system represents a powerful tool for a better understanding of the roles of chromosome architecture on transpositional recombination.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%